Fish spawning aggregations: where well‐placed management actions can yield big benefits for fisheries and conservation. Issue 1 (12th October 2015) - Erisman, Brad; Heyman, William; Kobara, Shinichi; Ezer, Tal; Pittman, Simon; Aburto‐Oropeza, Octavio; Nemeth, Richard S
Abstract: Marine ecosystem management has traditionally been divided between fisheries management and biodiversity conservation approaches, and the merging of these disparate agendas has proven difficult. Here, we offer a pathway that can unite fishers, scientists, resource managers and conservationists towards a single vision for some areas of the ocean where small investments in management can offer disproportionately large benefits to fisheries and biodiversity conservation. Specifically, we provide a series of evidenced‐based arguments that support an urgent need to recognize fish spawning aggregations (FSAs) as a focal point for fisheries management and conservation on a global scale, with a particular emphasis placed on the protection of multispecies FSA sites. We illustrate that these sites serve as productivity hotspots – small areas of the ocean that are dictated by the interactions between physical forces and geomorphology, attract multiple species to reproduce in large numbers and support food web dynamics, ecosystem health and robust fisheries. FSAs are comparable in vulnerability, importance and magnificence to breeding aggregations of seabirds, sea turtles and whales yet they receive insufficient attention and are declining worldwide. Numerous case‐studies confirm that protected aggregations do recover to benefit fisheries through increases in fish biomass, catch rates and larval recruitment at fished sites. The small size and spatio‐temporal predictability of FSAs allow monitoring, assessment and enforcement to be scaled down while benefits of protection scale up to entire populations. Fishers intuitively understand the linkages between protecting FSAs and healthy fisheries and thus tend to support their protection.